The Long-Term Costs of Government Surveillance: Insights from Stasi Spying in East Germany - Sebastian Siegloch; Andreas Lichter; Max Löffler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Based on official records from the former East German Ministry for State Security, we quantify the long-term costs of state surveillance on social capital and economic performance. Using county-level variation in the number of spies in the 1980s, we exploit discontinuities at state borders to show that higher levels of government surveillance led to lower levels of interpersonal and institutional trust in post-reunification Germany. Based on a second identification strategy that accounts for county fixed effects we further estimate the economic costs of spying. We find that a more intense surveillance caused lower self-employment rates, fewer patents per capita, higher unemployment rates and larger population losses throughout the 1990s and 2000s. Overall, our results suggest that the social and economic costs of East German state surveillance are large and persistent.
Keywords: H11; N34; P26; 330